Novel nonsense mutation of GPC3 gene in a patient with Simpson-Golabi-Behmel syndrome - Ratbi, Ilham; Elalaoui, Siham Chafai; Moizard, Marie-Pierre; Raynaud, Martine; Sefiani, Abdelaziz (The Turkish Journal of Pediatrics, 2010)
Simpson-Golabi-Behmel Syndrome (SGBS) is a rare recessive X-linked disorder characterized by pre- and postnatal overgrowth, distinctive dysmorphic facies and variable congenital malformations. Most cases have been attributed to mutations in the Glypican-3 (GPC3) gene located at Xq26. Glypican-3 plays essential roles in development by modulating cellular responses to growth factors and morphogens. We report here a novel nonsense mutation of the GPC3 gene in a five-year-old Moroccan patient of consanguineous parents who had SGBS phenotype associated with congenital hypothyroidism.